Both Intrinsic and Extrinsic Religious Orientation are Positively Associated with Attitudes Toward Cleanliness: Exploring Multiple Routes from Godliness to Cleanliness - Litman, Leib (Journal of religion and health, 2019)
In the present study, we explore how intrinsic and extrinsic religious orientations are associated with cleanliness attitudes. We find that reported importance of religion is associated with increased cleanliness concerns and interest in cleanliness. Attitudes toward cleanliness were also associated with both intrinsic religious orientation and extrinsic religious orientation. Together, religiosity and religious orientation account for 14.7% of cleanliness attitudes and remained significant in the presence of personality, socioeconomic status, age, education, obsessive-compulsive attitudes toward cleanliness, and other covariates. These results show that religiosity is associated with cleanliness via multiple routes. We suggest that intrinsic religious orientation leads to increased interest in cleanliness due to the link between physical and spiritual purity. Extrinsic religious orientation may be linked with cleanliness because of the secondary benefits, including health and the facilitation in communal cohesiveness, that cleanliness rituals offer. The implications of these findings for the relationship between religion and health are discussed.